Predictability of human pharmacokinetics of drugs that undergo hepatic organic anion transporting polypeptide (OATP)-mediated transport using single-species allometric scaling in chimeric mice with humanized liver: integration with hepatic drug metabolism. (1st November 2020) - Sanoh, Seigo; Naritomi, Yoichi; Kitamura, Satoshi; Shinagawa, Akihiko; Kakuni, Masakazu; Tateno, Chise; Ohta, Shigeru
Abstract: We previously reported a prediction method for human pharmacokinetics (PK) using single species allometric scaling (SSS) and the complex Dedrick plot in chimeric mice with humanized liver to predict the total clearance (CLt ), distribution volumes in steady state (Vdss ) and plasma concentration-time profiles of several drugs metabolized by cytochrome P450 (P450) and non-P450 enzymes. In the present study, we examined eight compounds (bosentan, cerivastatin, fluvastatin, pitavastatin, pravastatin, repaglinide, rosuvastatin, valsartan) as typical organic anion transporting polypeptide (OATP) substrates and six compounds metabolized by P450 and non-P450 enzymes to evaluate the predictability of CLt, Vdss and plasma concentration-time profiles after intravenous administration to chimeric mice. The predicted CLt and Vdss of drugs that undergo OATP-mediated uptake and P450/non-P450-mediated metabolism reflected the observed data from humans within a threefold error range. We also examined the possibility of predicting plasma concentration-time profiles of drugs that undergo OATP-mediated uptake using the complex Dedrick plot in chimeric mice. Most profiles could be superimposed with observed profiles from humans within a two- to threefold error range. PK prediction using SSS and the complex Dedrick plot in chimeric mice can be useful for evaluating drugs that undergo both OATP-mediated uptake and P450/non-P450-mediated metabolism.